Checklist of Peruvian Ichneumonidae (Insecta, Hymenoptera) - Rodríguez-Berrío, Alexander; Bordera, Santiago; Sääksjärvi, Ilari E. (Zootaxa, 2009)
A checklist of the Peruvian Ichneumonidae (Hymenoptera) is provided. A total of 391 species, in 134 genera and 20 subfamilies, are reported. Of these, 139 species are only known from Peru, and 48 represent undescribed species. This work reports nearly 53% more taxa than the checklist compiled by Francisco Carrasco (1972), representing a much needed update of that work. The checklist is updated to September 2009.